Al-Attas, Islamization and Pancasila: The Impact of Attasian Thought on Political Islam in Indonesia - Lilly, Peter (Universitas Islam Internasional Indonesia (UIII), 2024)
This article tracks the influence of specific ideas of the Malaysian Muslim philosopher Syed Muhammad Naquib Al-Attas on Indonesian Islamic political thought. The primary focus of the article is to outline the impact that the adoption of specific concepts from Al-Attas have had on the trajectory of Indonesian Islamic thought and Islamist politics. In particular, it focuses on how the concepts of Islamization and de-Islamization of language has helped bring about a new discourse on the relationship between Islam, Pancasila, and the state. This discourse has been led by a number of Indonesian Islamic political thinkers who studied the thought of Al-Attas in Malaysia and who have subsequently returned to Indonesia, hybridising and spreading these new ideas, exerting a great deal of influence on the Islamist movement in Indonesia.